2013
DOI: 10.1542/peds.2012-0820
|View full text |Cite
|
Sign up to set email alerts
|

Preventability of Early Readmissions at a Children’s Hospital

Abstract: Although initial consensus about which readmissions were more likely preventable was difficult to achieve, the overall rate of preventable pediatric 15-day readmissions was low. Pediatric readmissions are unlikely to serve as a highly productive focus for cost savings or quality measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 22 publications
6
73
0
Order By: Relevance
“…Consistent with previous research, 12 infections accounted for 20% of the reasons for return to acute care in this study. Respiratory decompensation, however, was the primary clinical reason for unplanned readmission to acute care in this sample.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous research, 12 infections accounted for 20% of the reasons for return to acute care in this study. Respiratory decompensation, however, was the primary clinical reason for unplanned readmission to acute care in this sample.…”
Section: Discussionsupporting
confidence: 92%
“…If a combined readmissions measure for common diseases was adopted, potential interventions could focus on delivering guideline-recommended care across similar diseases. Previous studies implementing care pathways and improving compliance with guidelines have reduced pediatric readmissions for bronchiolitis 35 and asthma, 36 although other studies have not shown improvements, 8,37 and thus additional work remains to be done. A pooled measure of readmissions for hospitals that admit a large number of complex chronically ill children, 38 who are known to be at risk for frequent readmissions, 2,3 could focus improvements specifically on these children during their transitions of care.…”
Section: Discussionmentioning
confidence: 99%
“…In the 15-day readmissions study by Hain et al, 28 readmissions after surgical hospitalizations were potentially preventable 39% of the time (significantly higher than after medical discharges [16%, P = .002]). 28 National samples by Berry et al 23 and Feudter et al 35 identified neuromuscular and neurologic disorders as the most common CCCs associated with 365-day readmissions, and they were the second most common 15-day readmissions in the study by Gay et al 31 Among studies including ACSCs, asthma was the most common ACSC 23,24,36 ; however, it is not known from these studies what fraction of the patients with asthma ACSC hospitalizations were medically complex.…”
Section: High-risk Conditionsmentioning
confidence: 98%
“…[27][28][29] Hain et al 28 devised a detailed 5-point Likert scale to rate preventability, which was independently applied by 4 physicians to chart reviews of 15-day readmission cases. They found that 20% of 15-day readmissions at their institution were potentially preventable, though overall agreement was difficult to achieve (and was specifically difficult in cases that were not clearly unpreventable).…”
Section: Preventable Hospitalizationmentioning
confidence: 99%
See 1 more Smart Citation